An Analysis of Validity and Reliability of a Teacher-Made Test - Agung Setiabudi; Mulyadi Mulyadi; Hilda Puspita (Journal of English Education and Teaching, 2019)
The aim of this research was to find out the validity and reliability of a teacher-made test in SMAN 6 Bengkulu. This research was a descriptive quantitative research. The subject of this research was an English teacher-made test for eleventh grade students of SMAN 6 Bengkulu. There were 40 items of the test consist of 35 multiple choice items and 5 essay items. There were two research instruments used in this research, observation checklist and documentation. Based on the data analysis, it was found that the  percentage of the validity score was 60% or 0.60. It means that the test was valid but in the intermediate category. The r-obtained for reliability test was 0.62 and it was considered to be reliable but was in the intermediate level of reliability.  From the research finding, it can be concluded that the test was valid and reliable but both were in the intermediate category. It means that the test still need some revision and improvement in order to be a good, valid, and reliable test. Key Words : Validity, Reliability, Teacher-made test